Urgensi Literasi Al-Qur’an Sebagai Tindakan Preventif Atas Penafsiran Yang Radikal - Moh. Akib (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2024)
This article explores the urgency of Al-Qur'an literacy as a preventive means of dealing with radical interpretations. By analyzing the role of Al-Qur'an literacy in a contextual and holistic understanding of the sacred text, this article highlights how important it is to have a deep understanding of religious teachings to prevent distorted interpretations. In the context of the digital era which is full of information that is easily spread, Al-Qur'an literacy is the key to distinguishing between correct understanding and the potential for dangerous interpretive radicalism. There is a need to study Al-Qur'an literacy in a broad and straightforward manner, not just following instant basics or a narrow understanding that can give rise to radicalism. The verses of the Qur'an must not only be understood literally, but also their context, meaning, and the most important teachings and lessons that can be learned from their interpretation. The Qur'an is a guide and guidance for human life that is not only read, but can be understood and applied in everyday life. By emphasizing the importance of inclusive and critical religious education, this article proposes concrete steps to strengthen Al-Qur'an literacy as an effort to prevent exegetical radicalism. It is hoped that Al-Qur'an literacy will have an influence not only on academic circles and ulama, but also on the general public with various public policies. Keywords: Literacy, Al-Qur'an, Preventive, Radical